A pilot study of the histo-morphological and loss of crystallites from human mineralised tissues due to daily consumption of everyday local Malaysian condiments. A radiological-variable pressure scanning electron microscope investigation. - Ghazali, Farid Che (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2004)
Local condiments consumption is a key constituent of diets throughout the east coast of Peninsular Malaysia. Little evidence-based knowledge's is known of the morphological changes that may impinge on oral health due to consumption of these local condiments. VPSEM, a new highly developed model of scanning electron microscope with simplified preparation of the tested material before use (Billy, 2000), has never been utilized before to study the effects of these locally available Malaysian condiments. This study is an attempt to pioneer the utility of high-resolution microscopy especially with VPSEM in elucidating a need to qualitate these condiments by scientific investigation thus, hoping to improve this commercially viable products present quality. At present their quality attributes is based mainly on flavor and smell.